How do we get from (x+3)(x+1) to ? We have already seen that 2(x+1) = 2x+2 We were able to do this multiplication by using the distributive property. We can also use the distributive property when we are multiplying polynomials by polynomials.
We need to remember to distribute each term in the first set of parentheses through the second set of parentheses. Example: (X+3)(x+1)=(x)(x)+(x)(1)+(3)(x)+(3)((1)
Lets work a few of these. 1.) (x+2) (x+8) 2.) (x+5) (x-7) 3.) (2x+4) (2x-3)
Check your answers. 1.) (x+2) (x+8) = X 2 +10x+16 2.) (x+5) (x-7) = X 2 -2x-35 3.) (2x+4) (2x-3) = 4x 2 +2x-12
By learning to use the distributive property, you will be able to multiply any type of polynomials. Example: (x+1)(x 2 +2x+3) (x+1)(x 2 +2x+3) = X 3 +2x 2 +3x+x 2 +2x+3